The literature of jealousy in the age of Cervantes - Wagschal, Steven, 1967- (University of Missouri Press, 2006)
"Explores the theme of jealousy in early modern Spanish literature through the works of Lope de Vega, Cervantes, and Gongora. Using the philosophical frameworks of Vives, Descartes, Freud, and DeSousa, Wagschal proposes that the theme of jealousy offered a means for working through political and cultural problems involving power"--Provided by publisher.